Genetic analysis of temperature-sensitive mutants which define the gene for the major herpes simplex virus type 1 DNA-binding protein. - Weller, S K (1983)
We have assigned eight temperature-sensitive mutants of herpes simplex virus type 1 to complementation group 1-1. Members of this group fail to complement mutants in herpes simplex virus type 2 complementation group 2-2. The mutation of one member of group 1-1, tsHA1 of strain mP, has been shown to map in or near the sequence which encodes the major herpes simplex virus type 1 DNA-binding protein (Conley et al., J. Virol. 37:191-206, 1981). The mutations of five other members of group 1-1 map in or near the sequence in which the tsHA1 mutation maps, a sequence which lies near the center of UL between the genes for the viral DNA polymerase and viral glycoprotein gAgB. These mutants can be divided into two groups; the mutations of one group map between coordinates 0.385 and 0.398, and the mutations of the other group map between coordinates 0.398 and 0.413. At the nonpermissive temperature mutants in group 1-1 are viral DNA negative, and mutant-infected cells fail to react with monoclonal antibody to the 130,000-dalton DNA-binding protein. Taken together, these data indicate that mutants in complementation groups 1-1 and 2-2 define the gene for the major herpes simplex virus DNA-binding protein, an early gene product required for viral DNA synthesis.